2016
DOI: 10.5539/jsd.v9n1p286
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Domestic Food Price Differentials: Constraints for Intra-Uganda Trade

Abstract: The paper estimates the determinants of price differentials across 79 districts in Uganda. In the framework of the law of one price, we examine the hypothesis that the spatial price differentials are at least partly influenced by transportation and other transaction costs, infrastructural constraints, productivity and commodity output shocks and the purchasing power of households. The study notes the wide range of price differences across the country, which to a large extent can be attributed to the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Although, climate differences across markets have a negative long-run impact on price differences. The finding is similar to previous finding by Shinyekwa and Ijjo (2016) for Ugandan markets. The authors also found that wide range of food price differences across markets are attributed to interaction between physical infrastructure and remoteness of markets.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…Although, climate differences across markets have a negative long-run impact on price differences. The finding is similar to previous finding by Shinyekwa and Ijjo (2016) for Ugandan markets. The authors also found that wide range of food price differences across markets are attributed to interaction between physical infrastructure and remoteness of markets.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…The classification of the goods created 5,395 tariff lines at the Harmonized System (HS) 8-digit level. Out of these, 2,003 (37%) accounted for the 0% band, 1,152 (21.4%) were for the 10% band, 2,176 (40.3%) were for the 25% band and 64(1.2%) were tariff bands that were greater than 25% (Shinyekwa & Katunze, 2016). These classifications of goods brought a general reduction in import tariffs in 2005 as seen in Figure 1.…”
Section: Import Tariffs the Eac-cet And Labor Incomesmentioning
confidence: 98%
“…Moreover, the market system is extremely dynamic: for example, a poor seasonal harvest in a market that typically supplies one intermediary marketplace may result in a shift of spatial supply chains in that intermediary marketplace to a wholly different region. By the time agricultural commodities reach the end consumer, many locally based determinants from intermediary marketplaces across the region are likely embedded in the final supply and price (Butler and Sinclair 2020; Shinyekwa and Ijjo 2016;Goletti et al 1995;Judge and Wallace 1958). Investigating the spatial distribution of market conditions throughout the economy then, is a rich area for analysts and researchers to develop policy-relevant insights that target East Africa's economic development, food security, and poverty reduction.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%